The late Victorian Navy : the pre-dreadnought era and the origins of the First World War - Parkinson, Roger (JSTOR EBA., 2008)
In purely naval terms, the period from 1889 to 1906 is often referred to (and indeed passed over) as the 'pre-Dreadnought era', merely a prelude to the lead-up to the First World War, and thus of relatively little importance; it has therefore received little consideration from historians, a gap which this book remedies by reviewing the late Victorian Navy from a radically new perspective. It starts with the Great Near East crisis of 1878 and shows how its aftermath in the Carnarvon Commission and its evidence produced a profound shift in strategic thinking, culminating in the Naval Defence Act of 1889; this evidence, from the ship owners, provides the definitive explanation of why the Victorian Navy gave up on convoy as the primary means of trade protection in wartime, a fundamental question at the time. The book also overturns many assumptions about the era, especially the perception that the navy was weak, and clearly shows that the 1870s and early 1880s brought in crucial technological developments that made the Dreadnought possible.